Manejo agroecológico de la negrita del tomate (Prodiplosis longifila) con la utilización de biocidas orgánicos de origen vegetal - Ronquillo Bravo, René Rolando (2022)
Tomato is one of the most consumed fruits worldwide, one of the main problems is the presence of the insect Prodiplosis longifila, which requires the intensive use of highly toxic pesticides. The objective of this research was to evaluate the effect of biocides obtained from dead rose, nettle, garlic and pyroleanic acid to control the attack of P. longifila on tomato crop. Trials were conducted to evaluate the effect of biocides on agronomic characteristics of the crop and to determine the biocide and dose with the highest efficacy in controlling P. longifila. A DBCA with 3 blocks and 14 treatments was used.